The Influence of Wordwall Learning Media on Improving Students’ Mathematics Learning Outcomes in Elementary Schools - Indrawati, Tuti; Trisniawati, T; Hadi, Windia; Nisa, Ana Fitrotun; Khosiyono, Banun Havifah Cahyo (IndoMath: Indonesia Mathematics Education, 2025)
Mathematics learning in elementary school faces challenges in improving student outcomes because of the conventional teaching methods. The limited integration of technology in the learning process results in low student engagement and suboptimal conceptual understanding. This study aims to determine the impact of using Wordwall learning media to improve the math learning outcomes of third-grade students. This research uses a quasi-experimental method with instruments in the form of test questions. Data collection techniques were carried out through tests and observations. This research was conducted at one of the elementary schools in the city of Yogyakarta, Indonesia. The research sample involved students in two classes; each class had 30 students. The research findings show that there is a difference in the average learning outcomes between the two classes. The experimental class obtained an average score of 89.60, while the control class achieved an average score of 83.33. The increase in the average score of the experimental class was higher than that of the control class. The results of this study it was found that the significance level of the research results is 0.013 < 0.05. It means that the use of Wordwall learning media affects students' mathematics outcomes.